2021
DOI: 10.1017/s0033583521000068
|View full text |Cite
|
Sign up to set email alerts
|

A molecular view of DNA flexibility

Abstract: DNA dynamics can only be understood by taking into account its complex mechanical behavior at different length scales. At the micrometer level, the mechanical properties of single DNA molecules have been well-characterized by polymer models and are commonly quantified by a persistence length of 50 nm (~150 bp). However, at the base pair level (~3.4 Å), the dynamics of DNA involves complex molecular mechanisms that are still being deciphered. Here, we review recent single-molecule experiments and molecular dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 214 publications
(306 reference statements)
1
37
0
Order By: Relevance
“…A review on DNA flexibility has recently been published by Marin‐Gonzalez et al 52 The authors cover a broad range of topics including the effect of chemical modifications, mismatches, transition between B and Z forms, or comparison to dsRNA. By contrast, in this work we mostly focus on structurally intact, chemically unmodified DNA in its B‐form.…”
Section: Introductionmentioning
confidence: 99%
“…A review on DNA flexibility has recently been published by Marin‐Gonzalez et al 52 The authors cover a broad range of topics including the effect of chemical modifications, mismatches, transition between B and Z forms, or comparison to dsRNA. By contrast, in this work we mostly focus on structurally intact, chemically unmodified DNA in its B‐form.…”
Section: Introductionmentioning
confidence: 99%
“…miR29b-1* mimic contains a centrally positioned AUAU-motif, which constitutes a 4 bp-long AU-tract, i.e., dsRNA sequences of alternating adenines and uracils. Molecular dynamics simulations and atomic force microscopy (AFM) have indicated that dsRNA AU-tracts induce a bend in the molecule due to a local compression of the major groove [ 62 , 75 ]. Such bend has been detected also in miR29b-1* [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the antiviral effects of the dsRNA miR29b-1* mimic were sequence-dependent, although the essential features of the sequence motifs necessary to activate RIG-I are still unclear. Interestingly, molecular dynamics simulations indicate that AU-tract motives in the context of GC-rich sequences give rise to dsRNA bending, owing to the collapse of the major groove located away from the sugar backbone, likely due to the lack of a hydrogen bond in AU compared to GC base pairs [ 62 , 75 ]. Additional simulations showed that changes in the major groove widths are correlated to minor groove changes by distinct geometrical alterations in the base pairs [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…MMR overall effectivity is proportional to the affinity of MutS to mismatched DNA, but some studies suggest that it is not the sole determinant in the efficiency of mismatch repair . While available data provided a general understanding of error recognition, individual mechanical factors responsible for its high efficacy are not fully understood. , …”
Section: Introductionmentioning
confidence: 99%
“…6 While available data provided a general understanding of error recognition, 7−12 individual mechanical factors responsible for its high efficacy are not fully understood. 13,14 MutS is a clamp-like dimer that encircles DNA and seeks errors along the double helix. 10,16 Published crystal structures showed how MutS captures a single nucleotide mismatch 11,17−23 and IDLs.…”
Section: ■ Introductionmentioning
confidence: 99%